Development of P301S tau seeded organotypic hippocampal slice cultures to study potential therapeutics - James M. McCarthy (Nature Portfolio, 2021)
Abstract Intracellular tau inclusions are a pathological hallmark of Alzheimer's disease, progressive supranuclear palsy, corticobasal degeneration and other sporadic neurodegenerative tauopathies. Recent in vitro and in vivo studies have shown that tau aggregates may spread to neighbouring cells and functionally connected brain regions, where they can seed further tau aggregation. This process is referred to as tau propagation. Here we describe an ex vivo system using organotypic hippocampal slice cultures (OHCs) which recapitulates aspects of this phenomenon. OHCs are explants of hippocampal tissue which may be maintained in culture for months. They maintain their synaptic connections and multicellular 3D architecture whilst also permitting direct control of the environment and direct access for various analysis types. We inoculated OHCs prepared from P301S mouse pups with brain homogenate from terminally ill P301S mice and then examined the slices for viability and the production and localization of insoluble phosphorylated tau. We show that following seeding, phosphorylated insoluble tau accumulate in a time and concentration dependent manner within OHCs. Furthermore, we show the ability of the conformation dependent anti-tau antibody, MC1, to compromise tau accrual in OHCs, thus showcasing the potential of this therapeutic approach and the utility of OHCs as an ex vivo model system for assessing such therapeutics.